Cervical Cancer Vaccination, A Step Towards Prevention : A Review - Chowdhury, Shahanara; Ferdous, Afroza (Journal of Chittagong Medical College Teachers’ Association, 2014)
Cervical cancer is the second most common cancer among women in the world. The human papilloma virus (HPV) was conclusively identified as the etiological factor for anogenital malignancy, including inducing cervical cancer. Investigations during the last two decades have been concentrating on producing a vaccine against HPV virus. Thus prevention of HPV infection has been the main purpose and vaccination is expected to reduce up to 70% of related cervical cancer and prevent precancerous and cancerous lesions of the genitalia. However, screening programs are still essential for those who have already been exposed to the high risk forms of the virus. Educational and information programs continue to play important roles to increase the success rate of screening. Two vaccines are now available for primary prevention. They generate neutralizing antibodies to HPV capsid protein. The vaccines have been shown to confer nearly 100 per cent protection against cervical pre-cancers and genital warts caused by HPV types 16/18 in HPV naive population with few or no side effects. Though there is some cross protection, around 30 per cent of cervical cancers will not be prevented by the vaccine. Vaccination and screening, which are complementary and synergistic, now constitute the new paradigm for prevention of this disease. JCMCTA 2013 ; 24 (2): 53-56